The ABCs of yoga for kids - Power, Teresa Anne; Rietz, Kathleen (Pacific Palisades, CA : Stafford House, 2009)
"The ABCs of Yoga for Kids" uses the alphabet, rhyming vignettes, and colorful illustrations to introduce children to yoga in a kid-friendly way. Features fifty-six different poses.
Keywords: Hatha yoga for children; Exercise for children; Yoga -- Juvenile literature; Exercise -- Juvenile literature; Yoga; Exercise